2014
DOI: 10.1007/s12288-014-0491-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Eltrombopag in Post-hematopoietic Stem Cell Transplantation (HSCT) Thrombocytopenia

Abstract: Twelve adult patients (median age 29.5 years) were started on Eltrombopag 25-50 mg/day for post-hematopoietic stem cell transplantation (HSCT) thrombocytopenia. All patients were having primary thrombocytopenia after HSCT. No patient had other secondary cause for thrombocytopenia. Two patients were allogenic subsets (1 acute myeloid leukemia i.e., AML and 1 aplastic anemia), and 10 were autologous transplants (3 multiple myeloma, 6 lymphoma and 1 AML). Nine patients were males, three were females. The median t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The previous reports using eltrombopag in allo-HSCT were summarized in Table 4. The 8 retrospective reports [12][13][14][15][16][17][18][19] have described a total of 31 patients who were treated with eltrombopag after allo-HSCT. Of these, 26 (83.9%) responded and became platelet transfusion independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous reports using eltrombopag in allo-HSCT were summarized in Table 4. The 8 retrospective reports [12][13][14][15][16][17][18][19] have described a total of 31 patients who were treated with eltrombopag after allo-HSCT. Of these, 26 (83.9%) responded and became platelet transfusion independent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that the same agent has been utilized as a therapeutic option for thrombocytopenia following allo-HSCT. However, literature on the use of eltrombopag after allo-HSCT has been sparse and limited to single case reports or case series [12][13][14][15][16][17][18][19], from which conclusions about the efficacy and safety of eltrombopag cannot easily be drawn. Additionally, until recently, there have been no data about the efficacy and safety of eltrombopag for refractory thrombocytopenia after haploidentical HSCT (haplo-HSCT), despite the fact that the current era has seen increasingly more haplo-HSCTs for patients without an HLA-matched sibling or unrelated donor [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, eltrombopag seems a good candidate agent to be investigated in the setting of post-HSCT thrombocytopenia or PoGF, which are obviously associated with a similar quantitative impairment of the HSC compartment [19]. Some few anecdotic cases have been described in the last 2 years; [24][25][26][27][28][29][30][31][32][33] however, data from clinical trials are not available, with the exception of a preliminary report from a phase II placebo-controlled randomized trial [34]. In this study, which enrolled 60 transplanted (53 allogeneic and 7 autologous) patients with persistent thrombocytopenia or neutropenia, the response rate in the experimental arm was 36%, but results were statistically inconclusive in terms of superiority in comparison with the control arm (28% responses) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Raut et al (16) reported an increase in the number of platelets with no side effects within 29 days on average by administering 25-50 mg/day eltrombopag to 12 patients with post-transplant primary thrombocytopenia, 2 patients allogeneic (AML, aplastic anemia), 10 patients autologous (MM, lymphoma, AML). Reid et al (8) reported that platelet levels were within the safe interval and patients no longer needed platelet infusion after administering 50 mg/day eltrombopag to two patients, one of which underwent allogeneic PSCT and the other autologous PSCT.…”
Section: Discussionmentioning
confidence: 99%